Effect of F8 B domain gene variants on synthesis, secretion, activity and stability of factor VIII protein - Pahl, Saskia; Pavlova, Anna; Driesen, Julia; Oldenburg, Johannes (Thrombosis and Haemostasis, 2014)
The B domain of the coagulation factor (F)VIII comprises some unique characteristics. Though the B domain is important for processing, intracellular transport and secretion of FVIII protein, its role in the coagulation still remains unclear. This study aims to investigate the influence of 19 reported B domain variants on quantity and quality of expressed FVIII protein. F8 variants were transiently expressed in HEK293T cells. Media and cell lysates were collected after 72 hours. FVIII synthesis, relative secretion, activity and thermostability were analysed in comparison to FVIII wild-type. Eleven of 19 analysed B domain variants showed normal FVIII activity (FVIII:C), and antigen values (40–150 %). Eight variants exhibited a decreased FVIII:C, corresponding to a mild phenotype most likely due to impaired expression and secretion mechanism, reduced thermostability or combined mechanisms. One variant, p.His1066Tyr, showed markedly reduced FVIII antigen in cell lysate. The variants p.Asp845Glu, p.His998Gln, and p.Ala1610Ser revealed a significantly decreased relative secretion. Additionally, six B domain variants significantly reduced stability of FVIII. In conclusion, none of the analysed missense mutations was causative for a severe haemophilia A (HA) phenotype. Nevertheless, the mutations p.Asp845Glu, p.Pro947Arg, p.Glu1057Lys, p.His1066Tyr, p.Arg1126Trp, p.Arg1329His, p.Leu1481Pro, and p.Ala1610Ser resulted in decreased FVIII:C values that may explain mild HA phenotypes.
Keywords: Factor VIII; B domain; missense mutation; genotype-phenotype relationship